Remaining Service Life Discharge Conveyor F pada Tambang Batubara PT GHI di Kabupaten Kotabaru, Provinsi Kalimantan Selatan - Syifa Kharenina; Elfida Moralista; Zaenal (Bandung Conference Series: Mining Engineering, 2023)
Abstract. Conveyor is a means of transportation used in the mining industry to transport minerals to make it more efficient. The conveyor structure is made of carbon steel which has the potential to experience oxidation reactions due to contact with the surrounding environment. The oxidation reaction that occurs causes the conveyor to corrode, thus causing a reduction in Remaining Service Life. Therefore, it is necessary to control and supervise corrosion on the conveyor structure so that Remaining Service Life can reach its design life. The purpose of this research is to determine the type of corrosion that occurs, the methods used for corrosion control, the corrosion rate, and the remaining service life. The research methodology used is measuring the thickness of the conveyor structure. The actual thickness measurement was carried out on a 92 meter conveyor structure with 25 test points divided into 3 segments. Measurements were made using an Ultrasonic Thickness Gauge TT 130. The environmental conditions in the study area in 2017-2021 with an average rainfall of 233,65 mm/year, an average air temperature of 26,96oC, and an average air relative humidity 84,54%. The type of corrosion that occurs is uniform corrosion. The corrosion control method used on the conveyor structure is a coating method with 3 layers system namely, primary coating using Seaguard 5000, intermediate coating using Sherglass FF, and top coating using Aliphatic Arcylic Modified Polyurethane. The corrosion rate of the coveyor structure is between 0.1767 – 0.3283 mm/year in the good category based on the relative corrosion resistance of steel. The service life of the conveyor structure is 6 years and based on calculations, the Remaining Service Life is 8,50 – 10,96 years. Thus it is estimated that 40% or 10 test points are not expected to reach the design life of 15 years. Abstrak. Conveyor merupakan alat transportasi yang digunakan pada industri pertambangan untuk mengangkut mineral agar lebih efisien. Struktur konveyor terbuat dari baja karbon yang berpotensi mengalami reaksi oksidasi akibat kontak dengan lingkungan sekitar. Reaksi oksidasi yang terjadi menyebabkan conveyor mengalami korosi sehingga menyebabkan Remaining Service Life berkurang. Oleh karena itu, diperlukan pengendalian dan pengawasan korosi pada struktur konveyor agar Remaining Service Life dapat mencapai umur rencana. Tujuan dari penelitian ini adalah untuk mengetahui jenis korosi yang terjadi, metode yang digunakan untuk pengendalian korosi, laju korosi, dan sisa umur pakai. Metodologi penelitian yang digunakan adalah mengukur ketebalan struktur conveyor. Pengukuran ketebalan sebenarnya dilakukan pada struktur konveyor sepanjang 92 meter dengan 25 titik uji yang dibagi menjadi 3 segmen. Pengukuran dilakukan dengan menggunakan Ultrasonic Thickness Gauge TT 130. Kondisi lingkungan di wilayah studi tahun 2017-2021 dengan curah hujan rata-rata 233,65 mm/tahun, suhu udara rata-rata 26,96oC, dan kelembaban relatif udara rata-rata 84,54 %. Jenis korosi yang terjadi adalah korosi seragam. Metode pengendalian korosi yang digunakan pada struktur conveyor adalah metode pelapisan dengan sistem 3 lapis yaitu, pelapisan primer menggunakan Seaguard 5000, pelapisan menengah menggunakan Sherglass FF, dan pelapisan atas menggunakan Aliphatic Arcylic Modified Polyurethane. Laju korosi struktur konveyor antara 0,1767 – 0,3283 mm/tahun dalam kategori baik berdasarkan ketahanan korosi relatif baja. Masa layan struktur conveyor adalah 6 tahun dan berdasarkan perhitungan, Sisa Masa Pakai adalah 8,50 – 10,96 tahun. Dengan demikian diperkirakan 40% atau 10 titik uji diperkirakan tidak akan mencapai umur rencana 15 tahun.